2017
DOI: 10.1139/cjpp-2016-0158
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and neuroprotective activity of boswellic acids in rotenone parkinsonian rats

Abstract: There is evidence that inflammation and oxidative stress contribute to the neurodegenerative changes observed in Parkinson's disease. Unfortunately, there is a lack of curative treatment for this debilitating movement disorder. Boswellic acids (BAs) are pentacyclic triterpene molecules of plant origin that have been utilized for treating many inflammatory conditions. The current study was conducted to explore the protective role of BAs against rotenone-induced experimental parkinsonism. Twenty-four rats were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…The BAs also have been shown to have an inhibitory effect on signal transducer and as an activator of transcription 3 (STAT3) protein. [ 132 ] STAT3 is a critical signaling molecule involved in downstream regulation of proinflammatory cytokines. [ 133 ] Therefore, inhibition of NF‐κB and STAT3 proteins may be potential targets for the treatment of rotenone‐induced neurotoxicity [ 132 ] (Figure 4).…”
Section: Protective Effects Of Natural Compounds Against Rotenone‐indmentioning
confidence: 99%
“…The BAs also have been shown to have an inhibitory effect on signal transducer and as an activator of transcription 3 (STAT3) protein. [ 132 ] STAT3 is a critical signaling molecule involved in downstream regulation of proinflammatory cytokines. [ 133 ] Therefore, inhibition of NF‐κB and STAT3 proteins may be potential targets for the treatment of rotenone‐induced neurotoxicity [ 132 ] (Figure 4).…”
Section: Protective Effects Of Natural Compounds Against Rotenone‐indmentioning
confidence: 99%
“…BAs were also reported to produce antioxidant and hepatoprotective effect against non-alcoholic fatty liver diseases produced after feeding rats with a high-fat diet [21]. One recent study demonstrated the neuroprotective effect of BAs in experimentally induced Parkinsonism in rats [22].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates good extraction and it also shows that the quality of oleo gum resin used for extraction is of very good quality. Earlier reports show that the boswellic acids in the extract varies from 65% to 0.03% in Boswellia serrata , the most widely used boswellia species (Ameen et al, 2017, Beghelli et al, 2017). There are no reports on the amount of boswellic acids present in Boswellia sacra used in Arabian countries.…”
Section: Discussionmentioning
confidence: 99%